Regulating Consumption for Sustainability? Why the European Union Chooses Information Instruments to Foster Sustainable Consumption. (May 2017) - Pollex, Jan
Abstract : In light of ever increasing usage of natural resources, the global discourse on sustainable development is increasingly emphasizing the crucial role of sustainable consumption and thus the contribution of individual consumers—rather than the traditionally focused corporate producers—to the protection of ecosystems. This paper investigates how the European Union (EU) addresses and characterizes consumers and how the framing of the consumers' role impacts on the design of sustainable consumption policy. Thus, this paper analyzes the relevance of target groups and their discursive construction for policymaking. Based on the analysis of central EU policy agendas providing the frame for consumer‐oriented environmental policy, the paper shows that the EU's sustainable consumption policy builds on an image of average‐rational consumers and a weak sustainable consumption perspective. Both constructions of reality subsequently frame the choice of soft policy instruments. The role of citizens (as opposed to only producers) and the image of average‐rational consumers who can be activated through information measures or incentives gained prominence in the EU—and in OECD countries generally—at a time of dissatisfaction with the performance of regulatory policy in the 1990s, hinting at the significance of contextual factors in understanding discursive shifts with their policy implications.